Synthesis of the C17–C30 Bis-THF Fragment of Iriomoteolide-13a via Intramolecular syn-Oxypalladation of 26-Ene-17,21,23,28-tetraol - Gao, Kai; Ma, Haichen; Yip, Tsz Chun; Zhao, Hui; Dai, Wei-Min (Synthesis, 2023)
The fully substituted C17–C30 bis-tetrahydrofuran fragment of the proposed structure of iriomoteolide-13a has been assembled via asymmetric dihydroxylation-SN2 cyclization of 19-mesyloxy-21-ene-26-yne and PdCl2-catalyzed syn-oxypalladation of 26-ene-17,21,23,28-tetraol as the key steps. The syn-oxypalladation process gave an 89:11 diastereoselectivity and tolerated the free poly-hydroxy groups in the highly functionalized substrate.
Keywords: allylic alcohol; iriomoteolide-13a; oxypalladation; propargylic alcohol; bis-tetrahydrofuran